Reference values of cardiac volumes, dimensions, and new functional parameters by MR: A multicenter, multivendor study. Issue 4 (29th August 2016) - Aquaro, Giovanni Donato; Camastra, Giovanni; Monti, Lorenzo; Lombardi, Massimo; Pepe, Alessia; Castelletti, Silvia; Maestrini, Viviana; Todiere, Giancarlo; Masci, Piergiorgio; di Giovine, Gabriella; Barison, Andrea; Dellegrottaglie, Santo; et al.
Abstract : Purpose: To define reference values of cardiac volumes, dimensions, and new morpho‐functional parameters normalized for age, gender, and body surface area by cine‐bSSFP (balanced steady‐state free‐precession) magnetic resonance (MR). Materials and Methods: We enrolled 308 healthy subjects subdivided by gender and by six age classes: class I, >15–20 years; class II, >20–30 years; class III, >30–40 years; class IV, >40–50 years; class V, >50–60 years; and class VI >60 years. Dimensional, volumetric and morpho‐functional parameters of the left (LV) and right (RV) ventricles were measured using cine‐bSSFP MRI at 1.5T. Results: The LV and RV end‐diastolic volume indexes (EDVi) were inversely related to age ( P < 0.0001 r  = –0.34 and P < 0.0001 r  = –0.37, respectively). In addition, the LV mass index decreased with age ( P  = 0.0004, r  = –0.21). The LV longitudinal shortening was not significantly different among groups: ≥15% in all populations (95% confidence interval [CI]: 16–31). The sphericity index measured in end‐diastole was higher in females than in males ( P < 0.03): the upper limit was 40% for males and 42% for females. The normality cutoff of LV global function index was ≥33% in males and ≥35% in females. The end‐diastolic volume (EDV) of RV and LV was balanced (RV/LV ratio 0.85–1.15) without differences in the population. The LV EDV/mass was 1.0–1.8 in males and 1.0–2.1 in females. Conclusion: This study provides potential age‐ and gender‐specific reference. Level of Evidence: 2 J. Magn. Reson. Imaging 2017;45:1055–1067